창원지역 일부 환아에서 혈청 비타민 D의 주된 급원과 신체적 성장과의 관계 - 강혜영(Haeyoung Kang); 허은실(Eunsil Her); 이경혜(Kyung-Hea Lee) (Korean journal of community nutrition, 2015)
Objectives: This study was conducted to investigate the effects of the sources of vitamin D (duration of exposure to sunlight, intake of major food sources for vitamin D or vitamin D supplements) on the serum 25-(OH) $D_3$ levels, and the physical growth of a child. Methods: Subjects were 296 children aged 1 to 5 years who visited S hospital located in Changwon City. Survey data collection was carried out by direct interview method, and the biochemical data were collected using hospital records. Results: The study subjects were divided into three groups according to their levels of serum 25-(OH) $D_3$ (deficient, relatively insufficient, sufficient) and their percentage were 48.3%, 44.3% and 7.4% respectively. The average concentration of serum 25-(OH) $D_3$ was $20.41{±}6.55ng/mL$, which was relatively insufficient. The average duration of exposure to sunlight was $58.86{±}49.18minutes/day$. A total score of vitamin D major food sources was 46.71 points (full marks 153), and the most frequently consumed food items were milk, eggs, and cheese. Thirty-four percent of the subjects took vitamin D supplements and their dose were $11.96μg/day$. Three vitamin D sources in sufficient group were higher than deficient or relatively insufficient group significantly. Intake of vitamin D supplements showed positive relation (+) and high explanation power ($R^2=0.288$) on serum 25-(OH) $D_3$ concentration, but intake of vitamin D major food sources (+) and the duration of exposure to sunlight (+) had a low explanation power ($R^2=0.068$). The relations between serum 25-(OH) $D_3$ concentration and physical growth (height and weight) were shown as negative (-), and their explanation powers were low as 7.3% and 5.9% respectively. Conclusions: This study results can be useful when discussing the intake standard of vitamin D and the effective intake method for children. In addition, it will be helpful to build the children's nutrition policy and to plan the nutrition education program to improve the vitamin D status in children.